KAJIAN PERUBAHAN KUALITAS AIR SUNGAI BUNTUNG AKIBAT PEMBUANGAN LIMBAH PETERNAKAN BABI DI DESA BANYURADEN GAMPING SLEMAN - Namastra Probosunu; Iwan Y.B. Lelana; Sudarmadji Sudarmadji (Jurnal Perikanan Universitas Gadjah Mada, 2003)
Buntung Stream is one of the tributaries of Bedog Stream. The Bedog Stream and its tributaries in Bayem, subdistrict of Kasihan to their upstream are categorized as river of B group. The activity of pig raising which have been carried out by some people in BanyuradenGampingSleman which throw away the wastes in this area likely to have effect on physical, chemical, and biological water qualities, especially coliform bacteria.The objectives of this research were to know the changes on the water quality of Buntung Stream due to pig raising waste disposal in BanyuradenGampingSleman and to give alternative solution to the problem. Observation were conducted on the physico-chemical and also biological water qualities of the stream at four stations: Station I (±800 m upstream of the waste disposal point), Station II (at the waste disposal point), Station III (±500 m downstream of the waste disposal point), and Station IV (±900 m downstream of the waste disposal point, before the encountering of Buntung and Bedog Stream). The samples were collected at the station between 09.00-12.00 a.m repeated 10 times during June-July 2001.Based on the data analyses, it could be drawn some conclusions as follows: the pig raising wastes disposal into Buntung Stream increased water discharge and quantities of coliform group and coliform feces. The waste disposal increased total dissolved solids, ammonia, and phosphate contents but decreased dissolved oxygen and pH of the water, and did not affect the water velocity, temperature, and nitrate content. In addition, BOD5 dissolved     oxygen, and the density of coliform bacteria in Buntung Stream after receiving the pig raising wastes disposal were beyond the B group of the water quality standard in the Special Province of Yogyakarta, whereas the content of total dissolved solids, pH, ammonia, and nitrate were still within the range of the water quality standard.